Is there such a thing as a ‘fair’ distribution of road space? - Nello-Deakin, Samuel (Journal of urban design, 2019)
In recent years, various reports and studies have provided quantified estimates of the distribution of road space among different transport modes in various cities worldwide. In doing so, and inspired by broader discussions on transport and urban justice, they have sought to point out the unfairness of existing patterns of road space distribution. Although intuitively tempting, this paper argues that appeals in favour of a 'fair' distribution of road space are inherently problematic. In order to illustrate this point, the distribution of road space in Amsterdam is measured using GIS cartography and discussed in relation to various transport-related indicators.